QoS Strategies for Wired Communication Networks in Urban Rail Transit Signaling System - XU Yongshun (Chengshi guidao jiaotong yanjiu)
Objective With the increase in data traffic and diversification of data types in urban rail transit signaling systems, higher demands are placed on reliability, real-time performance, and security. It is necessary to thoroughly investigate QoS (quality of service) strategies for wired communication networks in signaling system. Method Based on the actual data from signaling systems and the architecture of wired communication networks, an analysis is conducted on the service requirements of ATP (automatic train protection) and ATS (automatic train supervision) subsystem backbone networks in the signaling system, from perspectives of network bandwidth, bandwidth requirements of each service, and involved data terminals. Considering the transmission capacity, data processing efficiency, and fault tolerance of wired communication networks, an optimized QoS implementation strategy for the signaling system is proposed and tested to validate its effectiveness. Result & Conclusion The QoS strategy employs RSVP (resource reservation protocol) to reserve resources before establishing communication sessions, and configures appropriate DSCP (differentiated services code point) parameters to ensure controllable bandwidth usage for each service terminal. Priority processing of services on the backbone network switches is based on the IEEE 802.1p protocol. Simulation test results show that the QoS strategy effectively limits the traffic of individual terminals under extreme traffic conditions, preventing application unavailability caused by single terminal failure. This significantly improves the quality and performance of the signaling system, ensuring the safe and efficient operation of urban rail transit signaling systems.